Pile-up correction techniques for real-time dosimetry in photon radiotherapy - Miklavec, Mojca; Loher, Bastian; Savran, Deniz; Novak, Roman; Sirca, Simon; Vencelj, Matjaz (2012 IEEE Nuclear Science Symposium and Medical Imaging Conference Record (NSS/MIC), 2012)
In radiotherapy, accurate in vivo dose monitoring can improve overall success of treatment. For hadronic therapy, the approach is to measure residual radioactivity after the treatment. In the more widely used, gamma ray radiotherapy under 20 MV, dose monitoring in vivo is far more complicated, since the only way to measure irradiation accuracy is while linac is operating at extremely high dose rates. Linac's leakage outside the nominal beam can be as high as 10 11 photons per cm 2 s at 1 m, leading to a 2 Gcps event rate even on a small detector crystal (2 × 2 × 20 mm 3 LYSO).